2020
DOI: 10.1002/aws2.1174
|View full text |Cite
|
Sign up to set email alerts
|

Stannous chloride reduction–filtration for hexavalent and total chromium removal from groundwater

Abstract: Hexavalent chromium (Cr(VI)) reduction using stannous chloride (SnCl 2 ) has emerged as a possible alternative to chromium treatment technologies such as strong base anion exchange. In an effort to target not only Cr(VI) reduction but, ultimately, total chromium (Cr(T)) removal, SnCl 2 addition followed by rapid sand filtration was tested at the pilot scale on a groundwater with a naturally occurring Cr(VI) concentration of 0.090 mg/L. A SnCl 2 dose of 1.5 mg/L, followed by filtration, was able to consistently… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 18 publications
(56 reference statements)
2
8
0
Order By: Relevance
“…Following the reduction step during Fe(II)-RCF, excess Fe(II) is purposefully oxidized to Fe(III), or ferric hydroxide (Fe(OH) 3 (s)), by dissolved oxygen (DO) via aeration or free chlorine (Cl 2 ) addition, after which particulate Fe(OH) 3 (s) and Cr(OH) 3 (s) can be removed by filtration. In addition to improving filtration, the oxidation step also ensures compliance with the EPA/DDW secondary MCL (SMCL) for total iron (Fe(T)) of 0.3 mg/ L. For Sn(II), filtration is also the final step but Cr(VI) reduction results in Sn(II) oxidation to stannic tin (Sn(IV)), not a known coagulant, prior to forming stannic oxide (SnO 2 (s)), in which case Sn(II)-RF is a more appropriate term for the process (Kennedy et al, 2020). Oxidation of excess Sn(II) to Sn(IV) by DO or free Cl 2 is not currently required as there is no EPA/DDW MCL or SMCL for total tin (Sn(T)).…”
Section: History Of Reduction Coagulation Filtration For Hexavalent C...mentioning
confidence: 99%
See 3 more Smart Citations
“…Following the reduction step during Fe(II)-RCF, excess Fe(II) is purposefully oxidized to Fe(III), or ferric hydroxide (Fe(OH) 3 (s)), by dissolved oxygen (DO) via aeration or free chlorine (Cl 2 ) addition, after which particulate Fe(OH) 3 (s) and Cr(OH) 3 (s) can be removed by filtration. In addition to improving filtration, the oxidation step also ensures compliance with the EPA/DDW secondary MCL (SMCL) for total iron (Fe(T)) of 0.3 mg/ L. For Sn(II), filtration is also the final step but Cr(VI) reduction results in Sn(II) oxidation to stannic tin (Sn(IV)), not a known coagulant, prior to forming stannic oxide (SnO 2 (s)), in which case Sn(II)-RF is a more appropriate term for the process (Kennedy et al, 2020). Oxidation of excess Sn(II) to Sn(IV) by DO or free Cl 2 is not currently required as there is no EPA/DDW MCL or SMCL for total tin (Sn(T)).…”
Section: History Of Reduction Coagulation Filtration For Hexavalent C...mentioning
confidence: 99%
“…Another potential opportunity for cost savings could result from the use of Sn(II), or more specifically stannous chloride (SnCl 2 ). Recent research by Kennedy et al (2018Kennedy et al ( , 2020, Henrie et al (2019), andNguyen et al (2020) for several Cr(VI) containing groundwaters ($10-100 μg/L) confirmed the reduction times are likely less than 1 min for reduction of Cr(VI), independent of the initial Cr(VI) concentration, to below the California rescinded MCL of 10 μg/L. Lower Sn(II):Cr(VI) mass dose ratios than Fe(II) were also realized, approximately 11:1-18:1, while maintaining the filterability of particulate SnO 2 (s) and Cr(OH) 3 (s), albeit following filter ripening (Kennedy et al, 2020).…”
Section: Areas For Optimizationmentioning
confidence: 99%
See 2 more Smart Citations
“…The removal achieved was relatively higher. In addition, another study conducted by Kennedy et al, (2020) [ 23 ] found that the use of SnCl 2 together with rapid sand filtration in a pilot scale in the treatment of groundwater achieved a consistent removal of chromium (Cr) from the groundwater. Moreover, Zepeda et al, (2018) [ 24 ] applied the usage of tin oxide (SnO 2 ) synthesised from SnCl 4 , finding that it allowed the significant removal of both nickel (Ni 2+ ) and copper (Cu 2+ ) ions from an aqueous solution.…”
Section: Introductionmentioning
confidence: 99%